On the justification of architectural and structural type of research vessel = К обоснованию архитектурно-конструктивного типа научно-исследовательского судна - Solomentsev, O. I.; Соломенцев, О. И.; Gofman, A. A.; Гофман, А. А. (My University, 2015)
The analysis of architectural and structural types of the research vessels (RV) which are built and being built shows that twin hull ships with usual lines and small waterplane area (SWATH) can be used. Therefore, the reduction in the acoustic characteristics of the vessel is rather significant for the RV, since its main task is exploration of fish resources for subsequent work of fishing vessels, as well as for naval supporting research vessels. It is expected that the efficiency indicator is determined by the amount of information obtained as a result of the work of the RV. The method of obtaining the information resides in the RV inspecting the water column or the seabed. At that, the noise of the ship itself affects the operating radius of measuring devices. Thus, the approximate method is suggested. On the basis of it, the specified ultimate noise level for the SWATH can be estimated. The paper suggests the generalized dimensionless indicator of the propeller noise level; it depends on the velocity of the vessel, its draught and the characteristics of the propellers. With displacement being the same, the RV SWATH has significantly better noise level properties, mainly due to the recessed propellers, which makes this option more preferred than that of the RV. = Рассмотрено, при каких требованиях задания на проектирование научно-исследовательского судна будет целесообразным рассмотрение варианта катамарана с малой площадью ватерлинии.
Соломенцев, О. И. On the justification of architectural and structural type of research vessel = К обоснованию архитектурно-конструктивного типа научно-исследовательского судна / О. И. Соломенцев, А. А. Гофман // Shipbuilding & Marine Infrastructure. – 2015. – № 1 (3). – C. 132–141.
Keywords: small waterplane area twin hull (SWATH); research vessel; propeller noise; propeller cavitation; судно с малой площадью ватерлинии; научно-исследовательское судно; шум гребных винтов; кавитация гребных винтов